2019
DOI: 10.7759/cureus.4505
|View full text |Cite
|
Sign up to set email alerts
|

Best Location and Reader Role in Usage of Emergency Manuals During Critical Events: Experienced Emergency Manual Users’ Opinion

Abstract: Introduction Emergency manuals (EM) are an essential component of the response to critical events by healthcare providers, and there is strong evidence to support the benefits of utilizing EMs in crisis management. Despite the widespread utilization of EMs by providers, there is currently no national standardized protocol for EM usage, accompanied by a deficit in research on EM usage. To develop a protocol for EM utilization, factors such as the best location for EMs to be placed and the EM reader r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…EMs have been shown to improve the clinical outcome of critical events and reduce the incidence of missing key steps during crisis management [ 6 , 14 ]. EMs also increase teamwork, efficiency, collaboration, and confidence [ 9 - 11 , 14 - 16 ]. In the patient’s case, the use of an EM directly improved patient care and avoided any adverse event that may have occurred with selection of a different pharmacologic agent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMs have been shown to improve the clinical outcome of critical events and reduce the incidence of missing key steps during crisis management [ 6 , 14 ]. EMs also increase teamwork, efficiency, collaboration, and confidence [ 9 - 11 , 14 - 16 ]. In the patient’s case, the use of an EM directly improved patient care and avoided any adverse event that may have occurred with selection of a different pharmacologic agent.…”
Section: Discussionmentioning
confidence: 99%
“…Operating room emergency manuals (EMs) are cognitive aids that contain current, medically established guidelines on the management of specific perioperative critical events [ 8 ]. The use of operating room EMs has been shown to reduce medical error and maximize productivity by allowing healthcare providers, especially anesthesia professionals, to respond more confidently and collaboratively to critical events [ 9 - 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…An EM implementation plan should be based on the organizational culture and team attributes 1 . Implementation will need to address a variety of factors, such as where the EM should be located (e.g., quick access) and possible team member roles (e.g., dedicated reader to read the steps from the EM out loud) 1,2,7 . Agarwala indicated that having specific assigned roles will ultimately depend on how many people are available in the OR at the time of the crisis.…”
Section: Methodsmentioning
confidence: 99%
“…Safe patient care is dependent on having effective systems in place to achieve the best possible outcomes. This is especially important during uncommon clinical emergencies, such as a malignant hyperthermia (MH) crisis or cardiac arrest, during which a quick response will help improve outcomes for patients 1‐5 . One tool that is gaining popularity in the perioperative setting to support teams during crises is the emergency manual (EM), which is a set of cognitive aids or checklists to help guide decisions and decrease dependence on memory 1,3‐6 …”
mentioning
confidence: 99%
“…EMs also increase immediate access to resources and decrease reliance on rote memory alone [ 5 ]. The use of operating room EMs has been shown to allow anesthesia professionals to respond more confidently and accurately to critical events [ 5 - 9 ].…”
Section: Introductionmentioning
confidence: 99%